The Persuasiveness of political communication. Analysis of the parliamentary speech by Prime Minister Mateusz Morawiecki on the polexit (October 14, 2021 - Leśniczak, Rafał (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The undertaken study analyzes the persuasiveness of the speech of Prime Minister Mateusz Morawiecki, delivered on October 14, 2021, which concerned Poland’s presence in the structures of the European Union, in connection with the allegations of the polexit by opposition politicians. The politician’s speech noted the dominance of the persuasive strategy over the information strategy. As for the content of the speech, the politician’s communication strategy was focused around the program as well as political and ideological values. In the Prime Minister’s statement, the politician did not promote his own personnel offer. In Morawiecki’s speech, there were means of positive persuasion (with regard to the political activities of the United Right) and means of negative persuasion (with regard to the actions of the opposition).